Digestive abilities, amino acid transporter expression, and metabolism in the intestines of piglets fed with spermine. Issue 5 (10th March 2020) - Liu, Guangmang; Mo, Weiwei; Cao, Wei; Jia, Gang; Zhao, Hua; Chen, Xiaoling; Wu, Caimei; Zhang, Ruinan; Wang, Jing
Abstract: This study evaluated the effects of spermine supplementation on the digestion, transport, and metabolism of nutrients in the jejuna of piglets. Of the 80 piglets examined, 40 received 0.4 mmol/kg body weight spermine, and the other half were randomly distributed such that the restricted nutrient intake supplemented with the saline solution for 7 hr and 3, 6, or 9 days in pairs. Spermine supplementation increased the lipase and trypsin activities ( p  < .05), and spermine increased the mRNA levels of maltase, sucrase, and aminopeptidase N (APN) but decreased the lactase gene expression ( p  < .05). Moreover, spermine increased the mRNA expression levels of amino acid transporters ( p  < .05). Spermine increased the jejunum glycerolphosphocholine, lipid, and taurine levels and decreased the choline and amino acids levels ( p  < .05). In summary, spermine can promote the digestion, transport, and metabolism of nutrients in piglets. Practical applications: Meat, fish, dairy products, and fruits contain polyamines (i.e., spermine, spermidine, and putrescine). Spermine plays an important role in the cell proliferation, growth, and differentiation, and spermine supplementation can improve the growth of broilers, growth performance of early weaning piglets, and intestinal maturation. The results of this study suggest that spermine can improve the digestion, transport, and metabolism of nutrients in piglets. Abstract : Dietary spermine supplementation and its extended duration may improve digestion by increasing the levels of digestive enzymes and their gene expression levels; spermine intake can result in the high expression of amino acid transporters in the jejuna of piglets; and spermine supplementation can modulate lipid and amino acid metabolisms in the jejuna of piglets.